Intra-Coronary Administration of Tacrolimus Improves Myocardial Perfusion and Left Ventricular Function in Patients with ST-Segment Elevation Myocardial Infarction (COAT-STEMI) Undergoing Primary Percutaneous Coronary Intervention - Sung, Pei-Hsun (Acta Cardiol Sin, 2021)
BACKGROUND: Ischemia-reperfusion injury following acute ST-segment elevation myocardial infarction (STEMI) is strongly related to inflammation. However, whether intracoronary (IC) tacrolimus, an immunosuppressant, can improve myocardial perfusion is uncertain. METHODS: A multicenter double-blind randomized controlled trial was conducted in Taiwan from 2014 to 2017. Among 316 STEMI patients with Killip class ≤ 3 undergoing primary percutaneous coronary intervention (PCI), 151 were assigned to the study group treated with IC tacrolimus 2.5 mg to the culprit vessel before first balloon inflation, and the remaining 165 were assigned to the placebo group receiving IC saline only. The primary endpoint was percentage of post-PCI TIMI-3 flow. The primary composite endpoints included achievement of TIMI-3 flow, TIMI- myocardial perfusion (TMP) grade, or 90-min ST-segment resolution (STR). The secondary endpoints were left ventricular ejection fraction (LVEF) and 1-month/1-year major adverse cardio-cerebral vascular events (MACCEs) (defined as death, myocardial infarction, stroke, target-vessel revascularization or re-hospitalization for heart failure). RESULTS: Although post-PCI TIMI-3 epicardial flow and MACCE rate at 1 month and 1 year did not differ between the two groups, TMP grade (2.54 vs. 2.23, p < 0.001) and 90-min STR (67% vs. 61%, p < 0.001) were significantly higher in the tacrolimus-treated group than in the placebo group. The STEMI patients treated with tacrolimus also had significantly higher 3D LVEF and less grade 2 or 3 LV diastolic dysfunction at 9 months compared to those without. CONCLUSIONS: IC tacrolimus for STEMI improved coronary microcirculation and 9-month LV systolic and diastolic functions. However, the benefit of tacrolimus on clinical outcomes remains inconclusive due to insufficient patient enrollment.